Optimalisasi Kerja Sama Sekolah dan Orang Tua dalam Pembentukan Karakter Siswa Melalui Pendekatan Manajemen Jaringan - Hidayah, Amany (Jurnal Ilmiah Profesi Pendidikan, 2026)
Character education requires strong collaboration between schools and parents as part of the three educational centers. However, this collaboration is often hindered by communication barriers, parents' limited time, and inconsistent interaction between schools and families. This study aims to optimize school-parent collaboration in shaping students' character through a network management approach. This study employed a descriptive qualitative design. Data were collected through observations and interviews at TKII Al Abidin Karanganyar. The participants included the principal, teachers, parents, and students. The data were analyzed to identify collaboration practices, challenges, and the implementation of network management in character education. The findings indicate that effective collaboration is achieved through direct communication during student drop-off and pick-up, communication books, telephone conversations, and parents' active participation in school programs. The network management approach strengthens coordination among schools, parents, and the community, enabling the integration of key character values, including religiosity, nationalism, independence, cooperation, and integrity. Despite these positive outcomes, collaboration is still constrained by parents' limited availability and insufficient two-way communication. In conclusion, optimizing school-parent collaboration through a network management approach and continuous communication effectively supports the development of students' character, particularly in fostering discipline and responsibility. Strengthening partnerships among schools, families, and the community is essential to ensure sustainable and meaningful character education.